Rewiring neutral lipids production for the de novo synthesis of wax esters in Rhodococcus opacus PD630 - Lanfranconi, Mariana Patricia (2017)
Rhodococcus opacus PD630 accumulates significant amounts of triacylglycerols (TAG), but is not able to de novo synthesize wax esters (WE) from structural unrelated carbon sources, such as gluconate. In this study, strain PD630 was engineered to produce WE by heterologous expression of maqu_2220 gene, which encodes a fatty acyl-CoA reductase for the production of fatty alcohols in Marinobacter hydrocarbonoclasticus. Recombinant cells produced ca. 46% of WE and 54% of TAG (of total WE + TAG) from gluconate compared with the wild type, which produced 100% of TAG. Cell growth was not affected by the heterologous expression of MAQU_2220. Several saturated and monounsaturated WE species were produced by cells, with C18:C16, C16:C16 and C16:C18 as main species. The fatty acid composition of WE fraction in PD630maqu_2220 was enriched with C16:0, C18:0, whereas C16:0, C18:0 and C18:1 predominated in the TAG fraction. Significant amounts of WE and TAG were accumulated by PD630maqu_2220 from whey, an inexpensive waste material from dairy industries, without affecting cell biomass production. This is the first report on WE synthesis by R. opacus from gluconate, which demonstrates that lipid metabolism of this bacterium is flexible enough to assimilate heterologous components for the production of new lipid derivatives with industrial interest.